A Fresh Apple or a New Barrel: Business Ethics from an Individual to Corporate Level (European Journal of Marketing and Economics, 2024)
The moral nature of corporations has been discussed for a long time. But, since 2001, with enormous economic effects of the misconduct of some corporations this discussion gained another dimension, it moved into the public sphere, the subject became more sensitive. The anger and mistrust of the public toward business triggered legislators and corporations to take urgent action. For example, just after the collapse of Enron (2001) the American Congress passed the Sarbanes-Oxley Act (2002) that covers the responsibilities of boards of directors and requires compliance training at all levels. It also revived the old controversial arguments about the nature of business – whether the only purpose of business is to make profits, the relationship of business and ethics – whether business ethics is an oxymoron, and human nature – whether it is ‘bad apples’ or ‘bad barrels’. Yet, with new sets of regulations, in 2017, we are still witnessing the misconduct of corporations on a global scale. This article investigates the effectiveness of corporate efforts such as revisiting mission statements, polishing the codes of ethics and conducting training, by evaluating the nature of business, human nature and the understanding of ethics in the workplace. By looking through the lens of utilitarianism of ethical issues in business, I will argue that codes of ethics and ethics training are necessary but not sufficient. Within the scope of this paper I wish to pave the way to a holistic approach which is necessary and sufficient to create ethical businesses.
Keywords: Business ethics, code of ethics, training, bad apples, utilitarianism